An Amicable Divorce: Programmatic Derivation of Faceted Data from Library of Congress Subject Headings for Music. Issue 7 (3rd October 2018) - Mullin, Casey A.
Abstract: Music catalogers have embraced in current cataloging the flexibility, intuitiveness, and expressivity afforded by the Library of Congress's new faceted vocabularies. In order to realize the full benefits to discovery these vocabularies offer, however, methods for programmatically assigning faceted terms retrospectively to existing metadata for music resources are required in order to mitigate the costs of manual enhancement of legacy data. This article describes efforts to repurpose existing Library of Congress Subject Headings as faceted data, taking advantage of recent developments in the MARC 21 formats. Limitations inherent to this process and ideas for future directions are described.